2014
DOI: 10.1093/ckj/sfu048
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury due to decompression illness

Abstract: Decompression illness is a rare but serious complication of diving caused by intravascular or extravascular gas bubble formation. We report the first case of acute kidney injury in a 27-year-old diver following three rapid ascents. He presented with transient neurological symptoms and abdominal pain followed by rapidly progressive acute kidney injury (creatinine peak 1210 µmol/L) due to arterial air emboli. He received supportive care and 100% oxygen followed by hyperbaric therapy and recovered fully. Arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…advised treatment with plasma expanders such as albumin. 9 Crystalloids are widely used in the treatment of DCI 1013 as in our patient who, on discharge from ITU, had a haemoglobin of 93 g/l and haematocrit 28% after receiving 12 L of fluid in total.…”
Section: Discussionmentioning
confidence: 78%
“…advised treatment with plasma expanders such as albumin. 9 Crystalloids are widely used in the treatment of DCI 1013 as in our patient who, on discharge from ITU, had a haemoglobin of 93 g/l and haematocrit 28% after receiving 12 L of fluid in total.…”
Section: Discussionmentioning
confidence: 78%
“…Viecelli et al performed a renogram on a DCI patient with AKI; the result was compatible with that of acute tubular necrosis (ATN) [16]. In that case, the authors concluded that ATN was caused by DCI, not rhabdomyolysis, because CK was not remarkably high (maximum of 893 U/L) and myoglobinuria was negative [16]. In a case similar to ours, Kalpa et al reported a severe case of DCI with AKI that showed remarkable hemoconcentration (Hct 65%), indicating the existence of CLS [18].…”
Section: Discussionmentioning
confidence: 82%
“…We considered that rhabdomyolysis, secondary to AGE, was not the main cause of AKI in this case, because the patient had renal impairment and anuria, even with slightly elevated CK levels initially. Viecelli et al performed a renogram on a DCI patient with AKI; the result was compatible with that of acute tubular necrosis (ATN) [16]. In that case, the authors concluded that ATN was caused by DCI, not rhabdomyolysis, because CK was not remarkably high (maximum of 893 U/L) and myoglobinuria was negative [16].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation